Caring for Quine's Don't-Cares. - Pearson, James (Monist, 2017)
In Word and Object, W.V. Quine dismisses connotations that result from the work of explicating expressions as "don't-cares." This paper traces the history of this phrase to an algorithm that Quine developed in the 1950s, which became important in early computer engineering. Computer programmers eventually came to realize that it was in their best interests to abandon the "don't-care" attitude. Similarly, I argue that naturalists who properly appreciate the communal nature of their inquiries have reason to adopt a more careful approach when they propose and evaluate explications.